39.9k views
0 votes
Tan A-CotA÷Tan A + cot A​

User Aksiom
by
4.9k points

1 Answer

4 votes

Answer:


2\sin^2 A - 1

Explanation:


(\tan A - \cot A)/(\tan A + \cot A​) =


= ((\sin A)/(\cos A) - (\cos A)/(\sin A))/((\sin A)/(\cos A) + (\cos A)/(\sin A))


= (\sin A \cos A * ((\sin A)/(\cos A) - (\cos A)/(\sin A)))/(\sin A \cos A * ((\sin A)/(\cos A) + (\cos A)/(\sin A)))


= (\sin^2 A - \cos^2 A)/(\sin^2 A + \cos^2 A)


= (\sin^2 A - \cos^2 A)/(1)


= \sin^2 A - \cos^2 A

Since


\sin^2 A + \cos^2 A = 1

we know


\cos^2 A = 1 - \sin^2 A

we now substitute to get


= \sin^2 A - (1 - \sin^2 A)


= \sin^2 A - 1 + \sin^2 A)


= 2\sin^2 A - 1

User Yayitswei
by
5.3k points